The Effectivity of Playing Therapy on Communication and Social Development on Autistic Children - Sri Mulyani (PLACENTUM: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2021)
Background: Autism is a complex developmental disorder associated with communication, social interaction and imagination activity. Until now, the exact cause of autism has not been found, but several studies have found that autism is caused by viruses such as Rubella, Toxoplasmosis and the Morbili and Rubella (MMR) vaccine. The purpose of this study was to determine the effectiveness of play therapy on communication and social development in autistic children,Subjects and Methods: The research design used quasi-experimental design with one group pre and post-test design. The play therapy activity was in the form of forming a play group with 19 respondents with the therapist as a facilitator. The study was conducted in Febuary-March 2020. The statistical test technique that used in this study was the Paired T Test.Results: The communication and social development of autistic children before 2 months of receiving play therapy had an average value of 4.67 and the communication and social development of autistic children after 2 months of receiving play therapy had an average value of 7.2. Based on the results of data analysis using the Paired T Test, it was obtained p = 0.001 (p < 0.05) so Ho is rejected and it is proven that there is an effect between giving play therapy and communication and social development in autistic children.Conclusion: There is an influence between play therapy on improving communication and social development in autistic children. The average post-test score is greater than the average pre-test value, proving that play therapy can improve communication and social development in autistic children.